ANALISIS KEAMANAN SERVER DIGITAL LIBRARY DARI AKTIVITAS CYBER CRIME MENGGUNAKAN METODE OPEN WEB APPLICATION SECURITY PROJECT - Caniago, Koko; Sutabri, Tata (Jusikom : Jurnal Sistem Komputer Musirawas, 2023)
Analysis of Digital Library Server Security from Cybercrime Activities Using the Open Web Application Security Project Method at Bina Insan University Lubuklinggau, where this title was raised due to problems with the Bina Insan University Digital Library server security system which had been hacked by hackers so I am the thesis writer. feel the need to conduct research on the security of the Digital Library server at Bina Insan Lubuklinggau University to see security holes in the Digital Library server so that this security gap can later be closed and resolved so that cybercrime on the Digital Library server does not happen again. In analyzing the security of the Bina Insan University Digital Library server, I as a researcher use the Open Web Application Security Project method, where the Open Web Application Security Project method that I use is the Open Web Application Security Project Top 10 which is a guide that can be used to see weaknesses on the website server. which are easy to attack so with this guide we can also overcome the weaknesses that are owned by the website server itself so that it will be stronger to prevent cybercrime.